Regeneration of invariant natural killer T (iNKT) cells: application of iPSC technology for iNKT cell-targeted tumor immunotherapy - Takahiro Aoki; Shinichiro Motohashi; Haruhiko Koseki (BMC, 2023)
Abstract Invariant natural killer T (iNKT) cells are a subset of innate-like T cells restricted by a major histocompatibility complex (MHC) class I-like molecule, CD1d. iNKT cells express an invariant T cell receptor (TCR) encoded by Vα14 Jα18 in mice and Vα24 Jα18 in humans and are activated by recognizing glycolipid antigens, such as α-galactosylceramide (αGalCer), presented by CD1d. iNKT cells exhibit anti-tumor activity via their NK-like cytotoxicity and adjuvant activity. Although iNKT cell-targeted immunotherapy is a conceptually promising approach, we still found a technical hurdle for its clinical implementation which is mainly due to the low frequency of iNKT cells, particularly in humans. To compensate for this, we proposed to generate adequate numbers of clinically competent NKT cells from induced pluripotent stem cells (iPSCs) for cancer immunotherapy. Toward this goal, we first obtained the proof of concept (POC) for this approach in mice. We developed a technology to differentiate iPSCs into iNKT cells (iPSC-iNKT cells) and found iPSC-iNKT cells efficiently rejected a syngeneic experimental thymoma by inducing antigen-specific CD8 T cells. After achieving the POC in mice, we developed human iPSC-iNKT cells, which had a high correlation in their gene expression profiles with parental iNKT cells. Human iPSC-iNKT cells also exhibited anti-tumor activity and adjuvant activity for human NK cells in vivo. Based on this supporting evidence for the anti-tumor activity of human iPSC-iNKT cells, we began to generate good manufacturing practice (GMP)-grade iPSC-iNKT cells. As of now, the first-in-human clinical trial of iPSC-iNKT cell therapy is ongoing as a single-agent, dose-escalation study for patients with advanced head and neck cancer. Demonstration of the safety of iPSC-iNKT cell therapy may allow us to improve the strategy by further reinforcing the therapeutic activity of iPSC-iNKT, cells either by gene-editing or combinatorial use with other immune cell products such as dendritic cells. Sixteen years after the establishment of the iPSC technology, we are reaching the first checkpoint to evaluate the clinical efficacy of iPSC-derived immune cells.